2017
DOI: 10.1186/s12887-017-0793-0
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of associations between psychiatric symptoms and disorders and cerebral gray matter volumes in adolescents born very preterm

Abstract: BackgroundBeing born preterm with very low birthweight (VLBW ≤ 1500 g) poses a risk for cortical and subcortical gray matter (GM) abnormalities, as well as for having more psychiatric problems during childhood and adolescence than term-born individuals. The aim of this study was to investigate the relationship between cortical and subcortical GM volumes and the course of psychiatric disorders during adolescence in VLBW individuals.MethodsWe followed VLBW individuals and term-born controls (birth weight ≥10th p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 103 publications
2
19
0
3
Order By: Relevance
“…We observed an association between these SNPs and gray matter density in cortical areas involved in memory, attention, information processing, and decision-making, such as precuneus, superior and inferior temporal gyrus, frontal gyrus, and inferior parietal lobule, respectively (Shapiro et al, 2002;du Boisgueheneuc et al, 2006;Wallentin et al, 2006;Vickery and Jiang, 2009;Tops and Boksem, 2011). Clinical studies have been demonstrated that smaller volumes of frontal, parietal and occipital cortices were associated with the higher rates of ADHD (Botellero et al, 2017;Suffren et al, 2017). In fact, ADHD is a disorder associated with cognitive control and reward response.…”
Section: Discussionmentioning
confidence: 80%
“…We observed an association between these SNPs and gray matter density in cortical areas involved in memory, attention, information processing, and decision-making, such as precuneus, superior and inferior temporal gyrus, frontal gyrus, and inferior parietal lobule, respectively (Shapiro et al, 2002;du Boisgueheneuc et al, 2006;Wallentin et al, 2006;Vickery and Jiang, 2009;Tops and Boksem, 2011). Clinical studies have been demonstrated that smaller volumes of frontal, parietal and occipital cortices were associated with the higher rates of ADHD (Botellero et al, 2017;Suffren et al, 2017). In fact, ADHD is a disorder associated with cognitive control and reward response.…”
Section: Discussionmentioning
confidence: 80%
“… 52 After preterm birth, alterations in brain structure and connectivity persist beyond adolescence, 2 , 37 and functional correlates include reduced cognitive ability 53 and poorer psychosocial functioning. 54 More specifically, differences in amygdala volume and connectivity influenced fear processing and emotion recognition after preterm birth. 55 , 56 , 57 , 58 Here, amygdala volume correlated with both the degree and directionality of altered thermal sensitivity (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In verschiedenen cMRT-Studien wurden Schädigungsmuster im Gehirn der ehemaligen FG mit klinischen Auffälligkeiten korreliert. Im Bereich des Thalamus, der subkortikalen grauen Substanz und des okzipitalen und parietalen Kortex wurden verminderte Hirnvolumina gefunden, die die hohe Rate der Verhaltensprobleme, Gedächtnisstörungen und Störungen komplexer kognitiver und motorischer Funktionen der FG ursächlich erklären können (5,9).…”
Section: Schulprobleme Lernschwierigkeiten Und Teilleistungsstörungenunclassified